Customer-driven marketing strategy at Era Fabrique Sdn. Bhd. - Hashim, Haslinda; Raja Yusof, Raja Nerina; Hussin, Siti Rahayu; Abdullah, Aman Asnida (School of Business of Economics (SPE), Universiti Putra Malaysia (UPM), 2023)
This case is about Era Fabrique an interior design and furniture company established by Aman Asnida in 2001. Era Fabrique positions itself as a one stop interior solution centre, offering a complete range of design and build services for the transformation of property. Era Fabrique’s has always focused on their government institutions customers. Changes in the external factors (environment and industry) have brought some challenges and issues which affect Era Fabrique’s current business performance and may need them to re-assess their situation and review on their current marketing strategies.